Autogenous deformation induced- stress evolution in high-volume GGBFS concrete: Macro-scale behavior and micro-scale origin. (17th March 2023) - Liang, Minfei; Chang, Ze; Zhang, Yu; Cheng, Hao; He, Shan; Schlangen, Erik; Šavija, Branko
Highlights: The autogenous deformation and EAS of high-volume GGBFS concrete was tested by ADTM and TSTM. Early-age cracking risk of high-volume GGBFS concrete with different w/b ratios was analyzed. The optimal w/b ratio of high-volume GGBFS concrete regarding the early-age cracking was given. The microscale mechanisms were derived from material characterization tests. Abstract: This study aims to experimentally investigate the autogenous deformation and the stress evolution in restrained high-volume ground granulated blast furnace slag (GGBFS) concrete. The Temperature Stress Testing Machine (TSTM) and Autogenous Deformation Testing Machine (ADTM) were used to study the macro-scale autogenous deformation and stress evolution of high-volume GGBFS concrete with w/b ratios of 0.35, 0.42, and 0.50. The early-age cracking (EAC) risk (quantified by stress-strength ratio) and stress relaxation were analyzed extensively based on ADTM and TSTM results. Furthermore, Environmental Scanning Electron Microscopy (ESEM), X-ray Diffraction (XRD), and Mercury Intrusion Porosimetry (MIP) were conducted to explore the micro-scale origin of the autogenous deformation of high-volume GGBFS concrete, which supports the observations on the macroscale measurement of TSTM/ ADTM tests. This study finds that the ettringite formation in the first two days results in autogenous expansion, which can delay the appearance of tensile stress. The magnitude of autogenous expansion depends on the compatibility of ettringite content and pore size. The w/b ratio of 0.42 turns out to be optimal because it produces the highest amount of ettringite and results in the highest autogenous expansion. In comparison, the w/b ratio of 0.35 introduces significant autogenous shrinkage after the expansion peak and therefore corresponds to a high early-age cracking risk.